Celebrity Endorsers in Government Communication: A Plausible Option amidst Uncertainty and Declining Public Trust - Mohamad Alppy Valdez; Rendro Dhani (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2021)
This paper examines the harness of celebrity endorsers by government organizations as a strategy of political public relations. The purpose of this study was to broaden understanding of how celebrity endorsers and key opinion leaders work in the political realm, notably in supporting government policy. This descriptive-qualitative research uses a single case study on the promulgate efforts of the government’s COVID-19 vaccination program using celebrity endorsements. Literature research and social media material from a celebrity endorser were used as data collection techniques. To discover propaganda techniques, content analysis was performed on Raffi Ahmad’s social media posts. Next, a group discussion with six key informants was held to confirm the findings. Given the context and focus of this study lies on government organizations, we offer a different approach in examining celebrity endorsements by using propaganda theories and concepts. Kahneman’s dual-system theory of fast and slow thinking was also fruitful to rationalize the work of endorsement and relevant to propaganda and other persuasion theories. We found that the key messages that Raffi Ahmad published on his social media contained propaganda elements that had the potential to influence public opinion before making a decision. Therefore, the use of celebrity endorsements by government organizations is likely to be effective in influencing public behavior, or at least in raising awareness of government policies. We conclude that celebrity endorsement can be a plausible option to be implemented in the government communication strategy to achieve certain objectives.